p62 -mediated phase separation at the intersection of the ubiquitin-proteasome system and autophagy - Danieli, Alberto (J Cell Sci, 2018)
The degradation of misfolded proteins is essential for cellular homeostasis. Misfolded proteins are normally degraded by the ubiquitin-proteasome system (UPS), and selective autophagy serves as backup mechanisms when the UPS is overloaded. Selective autophagy mediates the degradation of harmful material by its sequestration within double membrane organelles called autophagosomes. The selectivity of autophagic processes is mediated by cargo receptors, which link the cargo to the autophagosomal membrane. The p62 cargo receptor has a major function during the degradation of misfolded, ubiquitinated proteins by selective autophagy; here it functions to phase separate these proteins into larger condensates and tether them to the autophagosomal membrane. Recent work has given us crucial insights into the mechanism of action of p62 during selective autophagy and how its activity can be integrated with the UPS. We will discuss these recent insights in the context of protein quality control and the emerging concept of cellular organization mediated by phase transitions.